2023
DOI: 10.1021/acs.jnatprod.2c01140
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Aggregation Inhibitory Procerolides and Diphenylalkanes from the Ascidian Polycarpa procera

Abstract: The aggregation of the neuronal protein α-synuclein (α-syn) is intrinsically linked to the development and progression of Parkinson's disease (PD). Recently we screened the MeOH extracts from 283 marine invertebrates for α-syn binding activity using an affinity mass spectrometry (MS) binding assay and found that the extract of the ascidian Polycarpa procera displayed activity. A subsequent bioassay-guided purification led to the isolation of one new α-syn aggregation inhibitory butenolide procerolide E (3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…The link between amyloid protein aggregation inhibition and antiplasmodial activity reported herein for 1 is particularly interesting since Biosca and co-workers reported functional amyloid-like aggregates in various life stages of Plasmodium parasites . Our previous research on natural product α-syn aggregation inhibitors has highlighted that compounds containing two or more 4-hydroxyphenyl groups show aggregation inhibition. , We have further found that the antiplasmodial activities of β-triketones are directly linked to the presence of a syncarpic acid group. The syncarpic acid may be present either as an acyclic moiety or embedded in a heterocycle.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The link between amyloid protein aggregation inhibition and antiplasmodial activity reported herein for 1 is particularly interesting since Biosca and co-workers reported functional amyloid-like aggregates in various life stages of Plasmodium parasites . Our previous research on natural product α-syn aggregation inhibitors has highlighted that compounds containing two or more 4-hydroxyphenyl groups show aggregation inhibition. , We have further found that the antiplasmodial activities of β-triketones are directly linked to the presence of a syncarpic acid group. The syncarpic acid may be present either as an acyclic moiety or embedded in a heterocycle.…”
Section: Resultssupporting
confidence: 57%
“…8 Our previous research on natural product α-syn aggregation inhibitors has highlighted that compounds containing two or more 4-hydroxyphenyl groups show aggregation inhibition. 11,47 We have further found that the antiplasmodial activities of β-triketones are directly linked to the presence of a syncarpic acid group. The syncarpic acid may be present either as an acyclic moiety or embedded in a heterocycle.…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…Prunolides D and E significantly inhibit the aggregation (>89%) of α-synuclein in a ThT amyloid dye assay . A Queensland collection of the ascidian Polycarpa procera provides the new procerolide E ( 141 ), methyl procerolate A ( 142 ), and the new natural product 3-bromo-4-methoxyphenylacetamide ( 143 ), previously known as a synthetic compound . Procerolides C, D and procerone A are described in ref .…”
Section: Tunicatesmentioning
confidence: 99%